The impact of measurement error on wage decompositions: Evidence from the British Household Panel Survey and the Household Income and Labour Dynamics in Australia Survey - S. C. Noah Uhrig; Nicole Watson (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Test-retest reliability assessments rarely investigate whether reliability itself is stable or whether change in reliability affects findings from substantive models. Research across the social sciences often recognises that measurement error could influence results, yet it rarely applies established error correction methods. Focusing on gender wage inequality, we address two questions. First, to what extent does reliability vary over time, across genders and across measurement protocols? Second, does correcting for measurement error influence substantive conclusions about gender wage inequality? Comparing British and Australian panel data, we find little temporal variability in reliability; however measurement error effects are variable and sometimes substantial.
Keywords: 330; British Household Panel Survey (BHPS); Household; Income and Labour Dynamics in Australia (HILDA) Survey; Measurement Error; Quasi-Simplex Models; Gender wage discrimination; Decomposition methods; Panel data